Brazil : Addressing the Challenge of Non-Communicable Diseases in Brazil - World Bank (Washington, DC, 2012)
Non-communicable diseases account for a large and growing share of Brazil's burden of disease. Currently, about 66 percent of the disease burden in Brazil is due to non-communicable diseases, compared to 24 percent from communicable diseases and 10% from injuries. Brazil's shift towards non-communicable diseases is a consequence of urbanization, improvements in health care, changing lifestyles, and globalization. Most of this disease burden i s not an inevitable result of a modern, aging society, but preventable-often at low cost. The purpose of this report is to provide an overview of the changing non-communicable disease burden in Brazil and its root causes, to examine costs and effectiveness of alternative policy interventions to address this growing burden, and the costs disease and potential returns from expanding non-communicable disease prevention and control activities, and to consider policy implication of expanding activities to effectively address the shifting burden.